2014
DOI: 10.1163/15736121-12341291
|View full text |Cite
|
Sign up to set email alerts
|

Global Citizenship Identification and Religiosity

Abstract: In four studies we examine the associations between religiosity, global citizenship identification, and various kinds of values (e.g., exclusionary, prosocial). Across the studies, general trends emerged showing that religiosity is unrelated to global citizenship identification, and positively related to exclusionary values (e.g., sexual prejudice, ethnocentrism, restricting outgroups). However, examination of the varied motivations to be religious (i.e., intrinsic, extrinsic, quest) showed that quest religiou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 34 publications
0
8
0
1
Order By: Relevance
“…Prosocial Values To assess prosocial values we used a series of short measures from prior research (Katzarska-Miller et al 2014;Plante et al 2014;Reysen and KatzarskaMiller 2013). Two items (e.g., BI am able to empathize with people from other countries^) assessed intergroup empathy (α=.62).…”
Section: Methodsmentioning
confidence: 99%
“…Prosocial Values To assess prosocial values we used a series of short measures from prior research (Katzarska-Miller et al 2014;Plante et al 2014;Reysen and KatzarskaMiller 2013). Two items (e.g., BI am able to empathize with people from other countries^) assessed intergroup empathy (α=.62).…”
Section: Methodsmentioning
confidence: 99%
“…Reysen, Katzarska‐Miller, and their colleagues have found several additional factors that positively predict GCI through one or both of the antecedents. These include the perception that culture is dynamic and fluid (Reysen & Katzarska‐Miller, ), thinking about a hoped‐for future possible self (Blake & Reysen, ), liberal political orientation, quest religious motivation (Katzarska‐Miller, Barnsley, & Reysen, ), higher grade‐point average, positive attitudes toward technology, participation in more social networks (Lee, Baring, Maria, & Reysen, ), and prior activism (Reysen & Hackett, ). While many prior variables may influence it, the model itself has been consistently replicated.…”
Section: Theoretical Foundations Of Global Human Identification and Cmentioning
confidence: 99%
“…GCI correlated negatively, −.14, with support for the war on terror (Reysen & Katzarska‐Miller, ). Katzarska‐Miller et al () found that GCI correlated .23 with a measure of desire for world peace. It also correlated .20 with attachment to one’s nation, but not to national glorification, r = .10, p >.05.…”
Section: Theoretical Foundations Of Global Human Identification and Cmentioning
confidence: 99%
“…In a series of studies based on natives and immigrants in Belgium, Saroglou and colleagues found that some of the (perhaps more intrinsic) aspects of religiosity were positively associated with identification as a world citizen (Saroglou & Galand, 2004;Saroglou & Hanique, 2006;Saroglou & Mathijsen, 2007). However, Katzarska-Miller et al (2014) and McFarland (2017), examining samples in the United States, found that religiosity had weak or non-significant correlations with identification as a global citizen (although intrinsic and quest religious motivations positively predicted global awareness). Roof (1976), by contrast, predicted and found that localism (or anti-cosmopolitanism) predicted higher religiosity in terms of both church attendance and religious beliefs among a Southern Protestant sample; this suggests a negative relationship between cosmopolitanism and religiosity.…”
Section: Different Aspects Of Religiositymentioning
confidence: 99%